PENGARUH CAMPURAN PATI JAGUNG DAN GLISEROL SEBAGAI EDIBLE COATING SIFAT FISIK DAN KIMIA ALPUKAT (Persea gratissima gaertn ) SELAMA PENYIMPANAN - Maya Sari; Firman Ganda Manik (Universitas Quality, 2018)
The research was conducted with the aim to determine the effect of the mixture between corn starch and glycerol as edible coating on the physical and chemical properties of avocados during storage. The study used a non factorial RAL (complete randomized design) method with the comparison of glycerol, corn starch and aquades as follows: G1 = 2.5ml glycerol + 10g corn starch + 500 ml aquades; G2 = 5ml glycerol + 10 g corn starch + 500 ml aquades; G3 = 7.5 ml glycerol + 10 g corn starch + 500 ml aquades; G4 = 10 ml glycerol + 10 g corn starch + 500 ml aquades. Each treatment was stored for 15 days with observations starting at 0 days, 3 days, 6 days, 9 days, 12 days, and 15 days. The giving of edible coating gave a significant effect on weight loss and sensory test of avocado during 15 days of storage, and gave no significant effect on total acid content and vitamin C content of avocados. Storage duration has an effect on weight loss and sensory test. The best edible coating layer in all concentration treatments was in treatment (G1) using 2.5 ml glycerol because it was better at inhibiting weight loss and changing the color of avocados.